2020
DOI: 10.1038/s41379-019-0434-2
|View full text |Cite|
|
Sign up to set email alerts
|

Assessment of individual tumor buds using keratin immunohistochemistry: moderate interobserver agreement suggests a role for machine learning

Abstract: Tumor budding is a promising and cost-effective biomarker with strong prognostic value in colorectal cancer. However, challenges related to interobserver variability persist. Such variability may be reduced by immunohistochemistry and computer-aided tumor bud selection. Development of computer algorithms for this purpose requires unequivocal examples of individual tumor buds. As such, we undertook a large-scale, international, and digital observer study on individual tumor bud assessment. From a pool of 46 col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(60 citation statements)
references
References 22 publications
(24 reference statements)
1
58
0
Order By: Relevance
“…Other studies comparing cytokeratin(only)-based assessments to H & E-based assessments demonstrated non superiority according to the prognostic value as well [12,13]. Small epithelial structures are straightforward to recognize on cytokeratin, but an elaborate study of experts has shown that the assessment of individual tumor buds using cytokeratin immunohistochemistry has just a moderate level of interobserver agreement, which indicates the issue with cytokeratin staining [14]. Using a supporting cytokeratin staining might be helpful in special situations, but a limitation of this study is that there was no standardized recording of qualitative factors (for example, inflammation).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies comparing cytokeratin(only)-based assessments to H & E-based assessments demonstrated non superiority according to the prognostic value as well [12,13]. Small epithelial structures are straightforward to recognize on cytokeratin, but an elaborate study of experts has shown that the assessment of individual tumor buds using cytokeratin immunohistochemistry has just a moderate level of interobserver agreement, which indicates the issue with cytokeratin staining [14]. Using a supporting cytokeratin staining might be helpful in special situations, but a limitation of this study is that there was no standardized recording of qualitative factors (for example, inflammation).…”
Section: Discussionmentioning
confidence: 99%
“…Scoring tumour budding according to the ITBCC method requires a bud count in a certain area, and this process, by its nature, requires time and training, and is subject to interobserver and intraobserver variation 11,12 . Interobserver variation in tumour budding assessment can be suboptimal, and depends on multiple factors, such as training and experience 13,14 .…”
Section: Automated Scoring Of Tumour Buds—where Do We Stand?mentioning
confidence: 99%
“…Most semi‐automatic tumour scoring methods have been developed with immunohistochemically stained slides, 11,12,15–21 in some cases with immunofluorescent staining 20,22,23 . Only one detection system has been proposed for H&E‐stained slides 24 …”
Section: Automated Scoring Of Tumour Buds—where Do We Stand?mentioning
confidence: 99%
See 2 more Smart Citations